The Influence of Audiovisual Education on Foot Care Compliance to Prevent Diabetic Ulcers in DM Type 2, Ngemplak Simongan Public Health Care - Aisyah, Siti Nur; Ismonah, Ismonah; Hartoyo, Mugi (Adi Husada Nursing Journal, 2025)
Audiovisual education is important to increase foot care compliance to prevent diabetic ulcers in DM Type 2 patients. This study examines the influence of audiovisual education on foot care compliance to prevent diabetic ulcers in DM Type 2. This is a quantitative research with a one-group pre-post-test quasi-experimental design at the working area of the Ngemplak Simongan Community Health Center. The sample consisted of 44 respondents selected by purposive sampling. Variables involved in this research are the audiovisual education and the foot care compliance. Foot care compliance was measured using the foot care compliance questionnaire. Based on the univariate analysis, the majority of respondents are female (72.2%), late elderly aged 56-65 years (43.2%), work as housewives (54.5%), and primary schooled (68.2%), also 50% suffered DMT2 for >5 years, 56.8% had hypertension complications, 79% did not smoke, and 33% did not have hypercholesterolemia history. The univariate analysis also stated that only 4.5% of respondents had foot care compliance behavior before intervention, then increased to 97.7% after intervention. Bivariate analysis stated that there is a significant influence of audiovisual education on compliance with foot care in people with type 2 DM at the Ngemplak Simongan Community Health Center, with p-value of 0.000. Healthy living practices can be influenced by appropriate health information. People with type 2 diabetes can try to avoid diabetic ulcers by learning about good foot care.